Micropropagation of tea (Camellia sinensis (L.) kuntze) using temporary immersion system - Gonbad, Reza Azadi (2012)
This research was carried out using tea clone Iran 100 with the aim of producing tea planting materials using temporary immersion system for accelerated mass production of true-to-type plants., Surface sterilization of nodal segment explants (from different positions) was tested using various exposure times to 20% Clorox. The highest survival of 60%was obtained for nodal segment two upon exposure to 20% Clorox for 15 minutes. All following experiments were carried out using nodal segment two. The response of nodal segment to shoot proliferation in solid MS media supplemented with two types of cytokinins namely 6-benzylaminopurine (BAP) at 0, 1, 3, 5 and 7 mg/L and thidiazuron (TDZ) at 0, 0.025, 0.05, 0.075 and 0.1 mg/L was studied. Gibberellic acid (GA3) at 0, 0.5 and 1 mg/L was included into the media with BAP and TDZ in order obtain multiplication and elongation at the same time. The results demonstrated that BAP was more effective as it was able to promote induction of shoots by reducing apical dominance in comparison to TDZ. Solid media which comprised of 3 mg/L BAP and 0.5 mg/L GA3 was the best, resulting in 7.5 shoots with average shoot length of 0.85 cm. Multiple subculture cycles (up to five times) using BAP did not show any adverse effect on shoot multiplication and the presence of BAP was necessary to retain the multiplication rate. In contrast,the effect of constant exposure to low concentration of TDZ stimulated callus formation and induced hyperhydricity. Upon establishment of proliferation in solid media, liquid culture system was tested both under shake and static condition with the use of BAP and TDZ in combination with GA3 at concentrations similar to those used for solid culture. Optimization of liquid culture system is important for use in temporary immersion system (TIS). Liquid culture with constant shaking gave better results in comparison to that maintained in static state. Liquid culture system also performed better compared to solid culture system with the production of 13.6 shoots per explant on medium containing 3 mg/L BAP + 0.5 mg/L GA3. The up-scaling of the mass propagation was carried out using the RITA bioreactor. Various immersion times of 60, 120 and 180 min were tested. RITA with immersion time of 120-minutes produced superior quality plantlets in terms of number of shoots (19) as well as plant morphology. An additional experiment was conducted to introduce the use of polypropylene containers for micropropagation of tea. Experimental results showed that in vitro mass propagation in polypropylene container played a significant role in terms of low cost-high efficiency regeneration system almost comparable to TIS in terms of number of shoot produced. The shoots produced using RITA was subjected to two rooting treatments namely continue and transfer. The study on in vitro rooting concluded that use of solid MS media supplemented with 5 mg/L IBA and subsequent transfer to growth regulator-free MS media resulted in highest percentage of root induction per explant (66.8%) and with a mean of 4.3 roots per explant. Contrastingly, MS media without hormones failed to induce rhizogenesis. Acclimatization was carried out using 4 different types of media; peat moss + vermiculite + perlite (2:2:0 v/v/v), peatmoss + vermiculite + perlite (1:2:1 v/v/v), peatmoss + vermiculite + perlite (1:1:2 v/v/v) and peatmoss + vermiculite + perlite (2:1:1 v/v/v). The best percentage of plant survival (84.5%) as well as best root length, height of plants and number of leaves was obtained in media which consist of peatmoss+ vermiculite+ perlite (2:1:1 v/v). Finally the genetic fidelity of the micropropaged tea plants wasssessed using ISSR (Inter-Simple Sequence Repeats). The amplified ISSR locus from 11 markers showed 100% similarity between micropropagated plants (derived in the third subculture of by TIS) and 10 randomly selected acclimatized plantlets with their mother plant DNA of tea clone Iran 100. The present study emphasizes that explants produced in the RITA® does not impede the clonal fidelity of in vitro regenerated propagules.